Penerapan Algoritma Knuth Morris Pratt Pada Fungsi Pencarian Arsip Dokumen Berbasis Web (Studi Kasus: Divisi Purchasing, PT Tifico Fiber Indonesia. TBK) - Habib; Ines Heidiani Ikasari (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The process of archiving documents in the purchasing division of TIFICO runs simply by saving hard copies of files to the bindex contained in the archive storage cabinet. As time goes by, documents will increase, so storing documents manually creates obstacles that make it difficult for staff when finding documents that are needed, thus making work less effective and efficient, besides that it can pose risks such as loss and damage to documents. In order for operations to run efficiently, a computerized archive management and search system is needed to integrate archive data into an integrated database, so that archives can be managed properly. In this study, the knuth morris pratt algorithm has been applied to the system search function to maximize the search process. The results of this study are in the form of a web-based archive management and search system, with a system that has been built the document archiving process to be more effective and efficient, this is evidenced by the test results with the average time needed by the Knuth Morris Pratt algorithm to search a document archive is 76.4 ms.